Methylotroph Infections and Chronic Granulomatous Disease - E. Liana Falcone; Jennifer R. Petts; Mary Beth Fasano; Bradley Ford; William M. Nauseef; João Farela Neves; Maria João Simões; Millard L. Tierce; M. Teresa de la Morena; David E. Greenberg; Christa S. Zerbe; Adrian Zelazny; et al. (Emerging Infectious Diseases, 2016)
Chronic granulomatous disease (CGD) is a primary immunodeficiency caused by a defect in production of phagocyte-derived reactive oxygen species, which leads to recurrent infections with a characteristic group of pathogens not previously known to include methylotrophs. Methylotrophs are versatile environmental bacteria that can use single-carbon organic compounds as their sole source of energy; they rarely cause disease in immunocompetent persons. We have identified 12 infections with methylotrophs (5 reported here, 7 previously reported) in patients with CGD. Methylotrophs identified were Granulibacter bethesdensis (9 cases), Acidomonas methanolica (2 cases), and Methylobacterium lusitanum (1 case). Two patients in Europe died; the other 10, from North and Central America, recovered after prolonged courses of antimicrobial drug therapy and, for some, surgery. Methylotrophs are emerging as disease-causing organisms in patients with CGD. For all patients, sequencing of the 16S rRNA gene was required for correct diagnosis. Geographic origin of the methylotroph strain may affect clinical management and prognosis.